Existence of travelling-wave solutions to a coupled system of Korteweg–de Vries equations. (November 2015) - Bhattarai, Santosh
Abstract: The purpose of this paper is to provide a mathematical proof of the existence of smooth solitary travelling waves for a coupled system of Korteweg–de Vries type equations u t + u x x x + ( u p v p + 1 ) x = 0, v t + r v x + v x x x + ( u p + 1 v p ) x = 0, where u = u ( x, t )